Sustainable stabilisation of organic soils using gypsum and concrete waste - Almsedeen, Ayah; Mohd Fakhrurrazi, Ishak; Nurmunira, Muhammad (Construction Research Institute of Malaysia, 2025)
Organic soils, with their low bearing capacity and high compressibility, present significant challenges in geotechnical engineering. This study investigated the stabilisation of organic soil using a novel combination of construction and demolition waste concrete waste (CW) and byproduct gypsum waste (G). Unconfined Compressive Strength (UCS) tests and Consolidated Undrained (CIU) triaxial compression tests were conducted to examine strength parameters and stress-strain behaviour under various conditions. The optimal mix of 10% CW and 10% G showed a 1108% strength increase after 28 days, while CIU triaxial tests demonstrated substantial improvements in shear strength and stiffness and reduced axial strain at failure. Test results revealed that higher confining pressure and longer curing times enhanced soil strength and reduced axial strain at failure. The combination of CW and G improved effective cohesion and friction angle, indicating better inter-particle bonding and mechanical performance. These findings highlight the potential of CW and G as sustainable, effective stabilisers for organic soil. The stabilisation increased the cohesion from 5–10 kPa to 20–30 kPa and enhanced the internal friction angle from 25° to 35–40°. This exhibits the effectiveness of CW and G in enhancing shear strength and mechanical properties, offering a greener alternative to traditional stabilisers in foundation design and construction